Scapular rotation to attain the peak shoulder external rotation in tennis serve - Konda, S.; Yanai, T.; Sakurai, S. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The purposes of this study were (a) to describe the detailed movements of the shoulder complex during the cocking phase in tennis serve and (b) to determine the contribution of the scapular rotation to the peak shoulder external rotation attained at the end of the cocking phase.